Integrated Mechanical, Thermal, Data, and Power Transfer Interfaces for Future Space Robotics - Yan, Xiu-Tian; Brinkmann, Wiebke; Palazzetti, Roberto; Melville, Craig; Li, Youhua; Bartsch, Sebastian; Kirchner, Frank (Frontiers in Robotics and AI, 2018)
Connection of modules in extra-terrestrial environment is a topic of rising importance in modern orbital or planetary missions. The increasing number of satellites sent to space has introduced a large set of connections of various type, for transferring mechanical loads, data, electrical power and heat from one module to another. This paper collects and presents the different transfer types developed and used to date in robotic applications for orbital and extra-terrestrial planetary missions. The aims of this paper are to present a detailed analysis of the available technology, and to make a useful comparison between different solutions to common problems, to make order in a complex, growing, important sector as it is that of connection in space. All types are described in their base characteristics and evaluated for orbital and planetary environments. This analysis shows that despite the large number of connectors developed for each of the four functionalities (mechanical, thermal, data and electrical power) here considered, the trend is that developers are integrating more than one into a single equipment or device, to reduce costs and improve standardisation. The outcome of this literature review has been used at the early stage of the Standard Interface for Robotic Manipulation of Payloads in Future Space Missions (SIROM) project, an H2020 funded project aiming to develop a multifunctional, standard, scalable interface to be employed in extra-terrestrial missions.